Modification of pea dietary fiber by ultrafine grinding and hypoglycemic effect in diabetes mellitus mice. Issue 4 (24th March 2021) - Wang, Meng; Chen, Xuanhong; Dong, Leichao; Nan, Xijun; Ji, Wei; Wang, Sai; Sun, Wanting; Zhou, Quancheng
Abstract : Abstract: This study was designed to investigate the effects of ultrafine grinding on the physicochemical properties of pea dietary fiber (PDF) and the hypoglycemic effect of ultrafine grinding dietary fiber on diabetes mellitus (DM). So, the PDF was treated by ultrafine grinding technology, and its microstructure and physicochemical properties were determined. Then, the DM model was established, and the 4‐week ultrafine grinded pea dietary fiber (UGPDF) diet intervention was conducted by using gavage and feeding. During this period, the blood glucose and body weight of the mice were measured, and an oral glucose tolerance test was measured on the last day. The biochemical blood indexes of the mice were determined, and the pancreas was stained with HE after dissecting. The results showed that after ultrafine grinding, the structure fragmentation, specific surface area increased, and UGPDF showed higher swelling ability as well as water and oil holding capacities. Simultaneously, UGPDF had a significant effect on reducing blood glucose and glycosylated hemoglobin in DM mice, improving the wasting state of mice and increasing the tolerance to glucose. Further, the results of the HE section showed that the pancreatic islet cells gradually returned to normal regular morphology. In biochemical blood indicators, UGPDF reduced TC and TG levels in the blood. This study provided a specific data basis for the following research on the hypoglycemic mechanism, and broadens the application field of PDF. Practical Application: The physicochemical properties of pea dietary fiber were improved by ultrafine grinding technology. Because of this, the application of pea dietary fiber in the field of hypoglycemic had a better effect, laying a foundation for the next research on hypoglycemic mechanism.